High-performance notebook computer shell composite material and preparation method thereof

By adopting a specific formula composite material formula and preparation process, the performance shortcomings of existing carbon fiber composite materials are solved, and high-performance laptop case composite materials with high mechanical properties, good flame retardancy, high temperature resistance and aging resistance are achieved.

CN119859406AActive Publication Date: 2025-04-22JIECHENG IND HUIZHOU CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510151848.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-22
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing carbon fiber composite laptop case still has room for improvement in mechanical and mechanical properties, flame retardancy, high temperature resistance and aging resistance.

Method used

The composite material formulas including carbon fiber, polyphenylene sulfide, functional polymers, coupling agents, nanotitanium dioxide, aluminum hydroxide flame retardant and benzylline bissulfonic acid were used, and high-performance laptop shell composite materials were prepared through powder impregnation and hot pressing molding.

Benefits of technology

It significantly improves the mechanical and mechanical properties, flame retardancy, high temperature resistance and aging resistance of composite materials. It has simple process and low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-performance notebook computer shell composite material and a preparation method thereof, and relates to the technical field of composite materials. Comprising the following raw materials in parts by weight: 20-30 parts of carbon fibers, 20-30 parts of polyphenylene sulfide, 10-20 parts of a functional polymer, 1-3 parts of a coupling agent, 3-5 parts of nano titanium dioxide, 1-3 parts of an aluminum hydroxide flame retardant, 2-4 parts of a catalyst A and 3-5 parts of benzidine disulfonic acid. The functional polymer comprises structural units introduced by the following monomers: 3, 3 '-diamino-4, 4'-difluorodiphenyl sulfone and 1, 4-cyclohexanedicarboxylic acid. The composite material has the advantages of favorable mechanical properties, favorable flame retardancy, excellent high-temperature resistance and excellent aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a high-performance laptop computer shell composite material and a preparation method thereof. Background Art

[0002] The laptop shell is not only the most direct way to protect the body, but also an important factor affecting its heat dissipation effect, weight, and aesthetics. With the rapid development of the laptop industry, laptop shells are also developing in the direction of high strength, high rigidity, and light weight. Traditional laptop shells are mostly made of alloys or engineering plastics. Although alloy shells have high strength, they generally have defects such as heavy weight, high cost, low wear resistance, and difficulty in molding, which affect user experience. Although engineering plastic shells are light and low in cost, they have low strength, easy deformation, and poor heat resistance, making it difficult to meet the needs of high-performance laptops. It is in this situation that carbon fiber composite shells came into being, and its appearance has attracted widespread attention in the industry.

[0003] Carbon fiber composite materials have many advantages such as high strength, high modulus, low specific gravity, low expansion coefficient, corrosion resistance, etc., and have both the high strength and firmness of aluminum-magnesium alloy and the plasticity of engineering plastics, making them excellent in comprehensive performance. However, the existing carbon fiber composite notebook shells still have more or less brittle surfaces, easy to break when dropped, high cost, slight leakage inductance if the grounding is not good, and high temperature resistance, flame retardancy and aging resistance need to be further improved.

[0004] In order to solve the above technical problems, the Chinese invention patent with application publication number CN119078216A discloses a carbon fiber composite material for a laptop computer shell and its preparation process, including the following processes: taking a carbon fiber cloth and laying it flat in a mold, coating an epoxy resin composition, precuring, and forming a precured carbon fiber layer; injecting a polyurethane resin on the upper surface and the lower surface of the precured carbon fiber layer in sequence to form a resin layer; molding to form a carbon fiber layer to obtain a carbon fiber composite material. The invention uses an epoxy resin composition made of epoxy resin and a curing agent to coat and impregnate the carbon fiber cloth to form a carbon fiber layer, so that it has the advantages of light weight, high strength, fast heat dissipation, and good shielding effect. A resin layer with high toughness is set on the upper and lower surfaces of the carbon fiber layer, which helps to improve the impact resistance of the prepared carbon fiber composite material. However, the mechanical properties, flame retardancy, high temperature resistance and aging resistance of the composite material still need to be further improved.

[0005] It can be seen that the art still needs a high-performance laptop computer shell composite material with good mechanical properties, good flame retardancy, excellent high temperature resistance and aging resistance, and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high-performance laptop computer shell composite material having good mechanical properties, good flame retardancy, excellent high temperature resistance and aging resistance and a preparation method thereof.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is: a high-performance laptop computer shell composite material, comprising the following raw materials in parts by weight: 20-30 parts of carbon fiber, 20-30 parts of polyphenylene sulfide, 10-20 parts of functional polymer, 1-3 parts of coupling agent, 3-5 parts of nano titanium dioxide, 1-3 parts of aluminum hydroxide flame retardant, 2-4 parts of catalyst A, and 3-5 parts of benzidine disulfonic acid; the functional polymer includes structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0008] Preferably, the carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , comes from Toray Industries, Japan.

[0009] Preferably, the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0010] Preferably, the preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, and catalyst B to a high boiling point solvent and mixing evenly to obtain a mixture, then adding the mixture to a reactor, replacing the air in the reactor with an inert gas, reacting at 120-130°C under normal pressure for 2-4 hours, then heating to 235-255°C, and performing a condensation reaction at 100-300 Pa for 15-22 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol 3-6 times, and then placing it in a vacuum drying oven at 85-95°C to dry to constant weight to obtain a functional polymer.

[0011] Preferably, the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B, and high boiling point solvent is 1:1:(0.8-1.2):(9-15).

[0012] Preferably, the high boiling point solvent is dimethyl sulfoxide; the inert gas is any one of nitrogen, helium, neon and argon; and the catalyst B is at least one of thiophosphonate, phosphorous acid and thiophosphoramide.

[0013] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0014] Preferably, the particle size of the nano titanium dioxide is 10-60 nm.

[0015] Preferably, the aluminum hydroxide flame retardant is at least one of aluminum oxide flame retardant VK-LA50 and aluminum oxide flame retardant VK-LA100.

[0016] Preferably, the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of (3-5):1.

[0017] Another object of the present invention is to provide a method for preparing the high-performance laptop computer shell composite material, comprising the following steps:

[0018] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 8-12 minutes to obtain a modified resin-based powder;

[0019] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0020] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0021] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0022] Preferably, the high temperature heat treatment in step S2 is performed at a temperature of 400-600° C. and for a time of 10-30 min.

[0023] Preferably, the power of the corona treatment in step S2 is 1-5KW, and the treatment time is 1-5min.

[0024] Preferably, in step S3, the temperature of the fluidized bed is 285-325° C., and the air flow velocity is 0.6-1.6 m / s.

[0025] Preferably, the hot pressing molding in step S4 is divided into two stages, the temperature of the hot pressing molding in the first stage is 170-180°C, the pressure is 8-12MPa, and the time is 3-5min; the temperature of the hot pressing molding in the second stage is 310-330°C, the pressure is 3-5MPa, and the time is 10-15min.

[0026] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0027] (1) The method for preparing the high-performance laptop computer shell composite material disclosed in the present invention has simple process, easy operation, low cost, high repeatability, adopts the powder impregnation method, does not need to use organic solvents, is environmentally friendly, is suitable for continuous large-scale production, and has high promotion and application value.

[0028] (2) The high-performance laptop shell composite material disclosed in the present invention comprises the following raw materials in parts by weight: 20-30 parts of carbon fiber, 20-30 parts of polyphenylene sulfide, 10-20 parts of functional polymer, 1-3 parts of coupling agent, 3-5 parts of nano titanium dioxide, 1-3 parts of aluminum hydroxide flame retardant, 2-4 parts of catalyst A, and 3-5 parts of benzidine disulfonic acid; the functional polymer comprises the following monomer introduced structural units: 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid. Through the mutual coordination and joint action of the raw materials, the product is endowed with advantages such as good mechanical properties, good flame retardancy, excellent high temperature resistance and excellent aging resistance. Using carbon fiber as the main reinforcement material can significantly improve the strength and modulus of the composite material; both the functional polymer and polyphenylene sulfide have excellent heat resistance and can meet the use requirements of laptop computers in high temperature environments. At the same time, they have good compatibility with fiber materials. Under the catalytic action of catalyst A, the sulfonic acid group on the benzidine disulfonic acid can react chemically with the benzene ring on the functional polymer and polyphenylene sulfide to solidify and form an interpenetrating network structure, thereby effectively improving the mechanical properties, flame retardancy, high temperature resistance and aging resistance of the product.

[0029] (3) The high-performance laptop computer shell composite material disclosed in the present invention, the functional polymer includes structural units introduced from the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid; fluorinated diphenyl sulfone, cyclohexane and amide structures are introduced at the same time. These structures, under the multiple effects of electronic effect, steric effect and conjugation effect, can further improve the flame retardancy, high temperature resistance and aging resistance of the product, improve the interface compatibility with fiber materials, and further improve the mechanical properties.

[0030] (4) The high-performance laptop computer shell composite material disclosed in the present invention, the addition of nano titanium dioxide and aluminum hydroxide flame retardants can not only play their own anti-ultraviolet and flame retardant properties, but also effectively improve the dimensional stability of the composite material, reduce thermal deformation, and ensure the accuracy and aesthetics of the laptop computer shell. DETAILED DESCRIPTION

[0031] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0032] Example 1

[0033] A high-performance laptop computer shell composite material comprises the following raw materials in parts by weight: 20 parts of carbon fiber, 20 parts of polyphenylene sulfide, 10 parts of functional polymer, 1 part of coupling agent, 3 parts of nano titanium dioxide, 1 part of aluminum hydroxide flame retardant, 2 parts of catalyst A, and 3 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0034] The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , which comes from Toray Industries, Japan; the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0035] The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, and catalyst B to a high boiling point solvent and mixing them evenly to obtain a mixture, then adding the mixture to a reactor, replacing the air in the reactor with an inert gas, reacting at 120°C for 2 hours at normal pressure, then heating to 235°C, and performing polycondensation reaction at 100 Pa for 15 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 3 times, and then drying it in a vacuum drying oven at 85°C to constant weight to obtain a functional polymer; the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B, and high boiling point solvent is 1:1:0.8:9; the high boiling point solvent is dimethyl sulfoxide; the inert gas is nitrogen; and the catalyst B is a thiophosphonate. Through GPC testing, the M of the functional polymer is n =15530 g / mol, M W / M n =1.372; through element quantitative analysis and weight change calculation, it is confirmed that the molar ratio of the structural units introduced by 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid in the functional polymer is the same as the theoretical value.

[0036] The coupling agent is silane coupling agent KH550; the particle size of the nano titanium dioxide is 10 nm; the aluminum hydroxide flame retardant is aluminum oxide flame retardant VK-LA50; and the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of 3:1.

[0037] A method for preparing the high-performance laptop computer shell composite material comprises the following steps:

[0038] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 8 minutes to obtain a modified resin-based powder;

[0039] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0040] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0041] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0042] The temperature of the high temperature heat treatment in step S2 is 400° C. and the time is 10 min. The power of the corona treatment in step S2 is 1 KW and the treatment time is 1 min.

[0043] The temperature of the fluidized bed in step S3 is 285°C and the air flow velocity is 0.6 m / s; the hot pressing molding in step S4 is divided into two stages, the temperature of the hot pressing molding in the first stage is 170°C, the pressure is 8 MPa, and the time is 3 min; the temperature of the hot pressing molding in the second stage is 310°C, the pressure is 3 MPa, and the time is 10 min.

[0044] Example 2

[0045] A high-performance laptop shell composite material comprises the following raw materials in parts by weight: 23 parts of carbon fiber, 23 parts of polyphenylene sulfide, 12 parts of functional polymer, 1.5 parts of coupling agent, 3.5 parts of nano titanium dioxide, 1.5 parts of aluminum hydroxide flame retardant, 2.5 parts of catalyst A, and 3.5 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0046] The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , which comes from Toray Industries, Japan; the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0047] The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid and catalyst B to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 123°C for 2.5 hours under normal pressure, then heating to 240°C, performing a polycondensation reaction at 150 Pa for 17 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 4 times, and then drying it in a vacuum drying oven at 87°C to constant weight to obtain the functional polymer; the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B and high boiling point solvent is 1:1:0.9:11; the high boiling point solvent is dimethyl sulfoxide; the inert gas is helium; and the catalyst B is phosphorous acid.

[0048] The coupling agent is silane coupling agent KH560; the particle size of the nano titanium dioxide is 30nm; the aluminum hydroxide flame retardant is aluminum oxide flame retardant VK-LA100; the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of 3.5:1.

[0049] A method for preparing the high-performance laptop computer shell composite material comprises the following steps:

[0050] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 9 minutes to obtain a modified resin-based powder;

[0051] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0052] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0053] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0054] The temperature of the high temperature heat treatment in step S2 is 450° C. and the time is 15 minutes; the power of the corona treatment in step S2 is 2KW and the treatment time is 2 minutes.

[0055] The temperature of the fluidized bed in step S3 is 295°C and the air flow velocity is 0.9 m / s; the hot pressing molding in step S4 is divided into two stages, the temperature of the hot pressing molding in the first stage is 173°C, the pressure is 9 MPa, and the time is 3.5 min; the temperature of the hot pressing molding in the second stage is 315°C, the pressure is 3.5 MPa, and the time is 12 min.

[0056] Example 3

[0057] A high-performance laptop computer shell composite material comprises the following raw materials in parts by weight: 25 parts of carbon fiber, 25 parts of polyphenylene sulfide, 15 parts of functional polymer, 2 parts of coupling agent, 4 parts of nano titanium dioxide, 2 parts of aluminum hydroxide flame retardant, 3 parts of catalyst A, and 4 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0058] The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , which comes from Toray Industries, Japan; the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0059] The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid and catalyst B to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 125°C for 3 hours under normal pressure, then heating to 245°C, performing a polycondensation reaction at 200 Pa for 19 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 5 times, and then drying it in a vacuum drying oven at 90°C to constant weight to obtain the functional polymer; the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B and high boiling point solvent is 1:1:1:12; the high boiling point solvent is dimethyl sulfoxide; the inert gas is neon; and the catalyst B is thiophosphoramide.

[0060] The coupling agent is silane coupling agent KH570; the particle size of the nano titanium dioxide is 40nm; the aluminum hydroxide flame retardant is aluminum oxide flame retardant VK-LA50; and the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of 4:1.

[0061] A method for preparing the high-performance laptop computer shell composite material comprises the following steps:

[0062] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 10 minutes to obtain a modified resin-based powder;

[0063] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0064] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0065] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0066] The temperature of the high temperature heat treatment in step S2 is 500°C and the time is 20 minutes; the power of the corona treatment in step S2 is 3KW and the treatment time is 3 minutes; the temperature of the fluidized bed in step S3 is 305°C and the air flow velocity is 1.1m / s.

[0067] The hot pressing molding in step S4 is divided into two stages. The temperature of the hot pressing molding in the first stage is 175°C, the pressure is 10MPa, and the time is 4min; the temperature of the hot pressing molding in the second stage is 320°C, the pressure is 4MPa, and the time is 13min.

[0068] Example 4

[0069] A high-performance laptop shell composite material comprises the following raw materials in parts by weight: 28 parts of carbon fiber, 28 parts of polyphenylene sulfide, 18 parts of functional polymer, 2.5 parts of coupling agent, 4.5 parts of nano titanium dioxide, 2.5 parts of aluminum hydroxide flame retardant, 3.5 parts of catalyst A, and 4.5 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0070] The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , which comes from Toray Industries, Japan; the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0071] The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid and catalyst B to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 128°C for 3.5 hours at normal pressure, then heating to 250°C, performing a polycondensation reaction at 250 Pa for 21 hours, then cooling to room temperature, adjusting to normal pressure, and evaporating in water. The crude product was precipitated, washed with ethanol for 5 times, and then dried in a vacuum drying oven at 93° C. to constant weight to obtain a functional polymer; the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B, and high boiling point solvent is 1:1:1.1:14; the high boiling point solvent is dimethyl sulfoxide; the inert gas is argon; the catalyst B is a mixture of thiophosphonate, phosphorous acid, and thiophosphoramide in a mass ratio of 1:2:3.

[0072] The coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570 in a mass ratio of 1:1:2; the particle size of the nano titanium dioxide is 35nm; the aluminum hydroxide flame retardant is a mixture of aluminum oxide flame retardant VK-LA50 and aluminum oxide flame retardant VK-LA100 in a mass ratio of 3:5; the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of 4.5:1.

[0073] A method for preparing the high-performance laptop computer shell composite material comprises the following steps:

[0074] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 8-12 minutes to obtain a modified resin-based powder;

[0075] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0076] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0077] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0078] The temperature of the high temperature heat treatment in step S2 is 550°C and the time is 25 minutes; the power of the corona treatment in step S2 is 4KW and the treatment time is 4 minutes; the temperature of the fluidized bed in step S3 is 315°C and the air flow velocity is 1.4m / s.

[0079] The hot pressing molding in step S4 is divided into two stages. The temperature of the hot pressing molding in the first stage is 178°C, the pressure is 11MPa, and the time is 4.5min; the temperature of the hot pressing molding in the second stage is 325°C, the pressure is 4.5MPa, and the time is 14min.

[0080] Example 5

[0081] A high-performance laptop shell composite material comprises the following raw materials in parts by weight: 30 parts of carbon fiber, 30 parts of polyphenylene sulfide, 20 parts of functional polymer, 3 parts of coupling agent, 5 parts of nano titanium dioxide, 3 parts of aluminum hydroxide flame retardant, 4 parts of catalyst A, and 5 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

[0082] The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 , which comes from Toray Industries, Japan; the model of the polyphenylene sulfide is 1150C, which is provided by Zhejiang Xinhecheng Co., Ltd.

[0083] The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid and catalyst B to a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material to a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 130°C for 4 hours under normal pressure, then heating to 255°C, performing a polycondensation reaction at 300 Pa for 22 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 6 times, and then drying it in a vacuum drying oven at 95°C to constant weight to obtain the functional polymer; the molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B and high boiling point solvent is 1:1:1.2:15; the high boiling point solvent is dimethyl sulfoxide; the inert gas is nitrogen; and the catalyst B is thiophosphoramide.

[0084] The coupling agent is silane coupling agent KH550; the particle size of the nano titanium dioxide is 60nm; the aluminum hydroxide flame retardant is aluminum oxide flame retardant VK-LA100; and the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of 5:1.

[0085] A method for preparing the high-performance laptop computer shell composite material comprises the following steps:

[0086] Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 12 minutes to obtain a modified resin-based powder;

[0087] Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber;

[0088] Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface;

[0089] Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

[0090] The temperature of the high temperature heat treatment in step S2 is 600°C and the time is 30 minutes; the power of the corona treatment in step S2 is 5KW and the treatment time is 5 minutes; the temperature of the fluidized bed in step S3 is 325°C and the air flow velocity is 1.6m / s.

[0091] The hot pressing molding in step S4 is divided into two stages. The temperature of the hot pressing molding in the first stage is 180°C, the pressure is 12MPa, and the time is 5min; the temperature of the hot pressing molding in the second stage is 330°C, the pressure is 5MPa, and the time is 15min.

[0092] Comparative Example 1

[0093] A high-performance laptop computer shell composite material and a preparation method thereof are basically the same as those in Example 1, except that an equal amount of polyphenylene sulfide is used instead of the functional polymer.

[0094] Comparative Example 2

[0095] A high-performance laptop computer shell composite material and a preparation method thereof are substantially the same as those in Example 1, except that no benzidine disulfonic acid is added.

[0096] In order to further illustrate the beneficial technical effects of the high-performance laptop computer shell composite materials involved in each embodiment of the present invention, relevant performance tests were conducted on the high-performance laptop computer shell composite materials involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows:

[0097] (1) Oxygen index: refer to GBT 8924-2005 for oxygen index test;

[0098] (2) Tensile strength: refer to GB / T 1447-2005 for tensile strength test;

[0099] (3) Heat deformation temperature: Refer to GB / T 1634.2-2004 for heat deformation temperature test;

[0100] (4) Aging resistance: Each product was placed in a forced air drying oven at 85°C for 100 h. After cooling to room temperature, the tensile strength was tested again using the method in (2). The tensile strength retention rate was statistically calculated. The larger the value, the better the aging resistance.

[0101] Table 1

[0102] project Oxygen Index Tensile Strength Heat Deflection Temperature Aging resistance unit % MPa ℃ % Example 1 35.8 2730 270 98.89 Example 2 36.2 2780 275 99.13 Example 3 37.0 2810 278 99.35 Example 4 37.3 2870 280 99.60 Example 5 37.8 2915 283 99.91 Comparative Example 1 34.2 2700 274 95.17 Comparative Example 2 33.6 2550 262 96.53

[0103] As can be seen from Table 1, the high-performance laptop computer shell composite material involved in the embodiment of the present invention has higher mechanical properties, flame retardant properties, high temperature resistance and aging resistance than the comparative example product; the combined use of functional polymer and benzidine disulfonic acid is beneficial to improving the above properties.

[0104] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance laptop computer shell composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of carbon fiber, 20-30 parts of polyphenylene sulfide, 10-20 parts of functional polymer, 1-3 parts of coupling agent, 3-5 parts of nano titanium dioxide, 1-3 parts of aluminum hydroxide flame retardant, 2-4 parts of catalyst A, and 3-5 parts of benzidine disulfonic acid; the functional polymer comprises structural units introduced by the following monomers: 3,3'-diamino-4,4'-difluorodiphenyl sulfone and 1,4-cyclohexanedicarboxylic acid.

2. The high-performance laptop computer shell composite material according to claim 1, characterized in that: The carbon fiber is carbon fiber cloth CO6644B, with a thickness of 0.3 mm and a gram weight of 317 g / m 2 ; The model of the polyphenylene sulfide is 1150C.

3. The high-performance laptop computer shell composite material according to claim 1, characterized in that: The preparation method of the functional polymer comprises the following steps: adding 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid and catalyst B into a high boiling point solvent and mixing them evenly to obtain a mixed material, then adding the mixed material into a reaction kettle, replacing the air in the kettle with an inert gas, reacting at 120-130°C for 2-4 hours at normal pressure, then heating to 235-255°C, performing a polycondensation reaction at 100-300 Pa for 15-22 hours, then cooling to room temperature, adjusting to normal pressure, precipitating in water, washing the crude product with ethanol for 3-6 times, and then drying it in a vacuum drying oven at 85-95°C to constant weight to obtain the functional polymer.

4. The high-performance laptop computer shell composite material according to claim 3, characterized in that: The molar ratio of the 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 1,4-cyclohexanedicarboxylic acid, catalyst B, and high boiling point solvent is 1:1:(0.8-1.2):(9-15); the high boiling point solvent is dimethyl sulfoxide; the inert gas is any one of nitrogen, helium, neon, and argon; and the catalyst B is at least one of thiophosphonate, phosphorous acid, and thiophosphoramide.

5. The high-performance laptop computer shell composite material according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570; the particle size of the nano titanium dioxide is 10-60nm.

6. The high-performance laptop computer shell composite material according to claim 1, characterized in that: The aluminum hydroxide flame retardant is at least one of aluminum oxide flame retardant VK-LA50 and aluminum oxide flame retardant VK-LA100; the catalyst A is a mixture of phosphorus pentoxide and polyphosphoric acid in a mass ratio of (3-5):

1.

7. A method for preparing a high-performance laptop computer shell composite material according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, mixing and grinding polyphenylene sulfide, functional polymer, coupling agent, nano titanium dioxide, aluminum hydroxide flame retardant and benzidine disulfonic acid, and performing surface treatment in a high-speed mixer for 8-12 minutes to obtain a modified resin-based powder; Step S2, subjecting the carbon fiber to high temperature heat treatment and then to corona treatment to obtain modified carbon fiber; Step S3, uniformly dispersing the modified resin-based powder in a fluidized bed, passing the modified carbon fiber through the fluidized bed at a certain speed, so that the resin-based powder is uniformly attached to the surface of the carbon fiber, and obtaining a carbon fiber with the resin-based powder attached to the surface; Step S4, evenly placing half the mass of catalyst A on the surface of the lower mold of the mold, then cutting the carbon fiber with resin-based powder attached to the surface into a desired shape, laying it in the mold, and then evenly placing the other half the mass of catalyst A on the carbon fiber with resin-based powder attached to the surface, closing the mold, hot pressing and molding, cooling and demolding to obtain a high-performance laptop computer shell composite material.

8. The method for preparing a high-performance laptop computer shell composite material according to claim 7, characterized in that: The temperature of the high temperature heat treatment in step S2 is 400-600°C, and the time is 10-30 minutes; the power of the corona treatment in step S2 is 1-5KW, and the treatment time is 1-5 minutes.

9. The method for preparing a high-performance laptop computer shell composite material according to claim 7, characterized in that: In step S3, the temperature of the fluidized bed is 285-325° C., and the air flow velocity is 0.6-1.6 m / s.

10. The method for preparing a high-performance composite material for a notebook computer shell according to claim 7, characterized in that: The hot pressing molding in step S4 is divided into two stages. The temperature of the hot pressing molding in the first stage is 170-180°C, the pressure is 8-12MPa, and the time is 3-5min; the temperature of the hot pressing molding in the second stage is 310-330°C, the pressure is 3-5MPa, and the time is 10-15min.

Citation Information

Patent Citations

  • Carbon fiber composite material for notebook computer shell and preparation process of carbon fiber composite material

    CN119078216A

  • Flame Retardant Polyamide Resin Composition And Molded Article Comprising The Same

    CN103910993A

  • Modified PET plastic and preparation method thereof

    CN118185252A

  • Waterproof anticorrosive paint as well as preparation method and application thereof

    CN119410240A

  • Conductive thermosetting resin composition and housing for electric and electronic apparatus

    JP1996311242A